Nursing Education Interventions on Anxiety, Knowledge, and Self-Care in Cataract Surgery Patients: A PRISMA-Based Systematic Review (2021 and 2025) - Asep Muhamad Nurhalim; Yunie Armiyati; Chanif Chanif (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: The success of cataract surgery depends not only on surgical techniques but also on patients’ physical and psychological preparedness. Perioperative nursing education plays a crucial role in reducing anxiety, improving knowledge, and enhancing self-care abilities. Objective: To evaluate the effectiveness of nursing education interventions on clinical and psychosocial outcomes in ophthalmic surgery patients. Methods: Systematic reviews are compiled based on the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Searches were conducted on PubMed, ScienceDirect, ProQuest, and Scopus (2021–2025) for quantitative studies (RCTs, quasi-experimental, pre-experimental) involving adult cataract surgery patients. A total of 92 articles were screened, leaving 8 articles that met the inclusion criteria and were analyzed. The methodological quality of each study was assessed with the Joanna Briggs Institute Critical Appraisal Checklist. Results: Nursing education delivered through face-to-face, printed materials, videos, audio, and mobile applications consistently reduced preoperative anxiety, increased patient knowledge, improved coping mechanisms and self-care abilities, and enhanced patient satisfaction. Digital media, especially videos and mobile applications, were found to be effective and practical. Conclusion: Nursing education is an essential component of perioperative care for cataract patients, improving psychological readiness, self-care, and overall patient experience.